The Court of Cassation of Discrimination on the Reality and the Law in the Criminal Case - الحيدري, جمال أبراهيم; حسن, ختام فليح (Journal of Legal Sciences, 2019)
The Court of Cassation is a court of law that monitors the lower courts by reviewing the judgments and decisions issued by these courts, and the fact that their control is on the side of the legal to judge the penal. It monitors the commitment of the courts' compliance with the proper and formal rules of law. In some cases, are errors chop terms and criminal to the facts of the case are subject to the jurisdiction of the Court of Cassation and not to the Court of Cassation, except to the extent that they cause the provisions through which the Court of Cassation can impose control over the facts of the criminal case and the outcome of the Court topic The subject of the results, and thus the legal aspect of the criminal case is the place to control either the Court of Cassation in which the real side Frkabtha be limited to the provisions of the reasons.